Sosialisasi Penggunaan Geo-Augmented Reality untuk Pembelajaran Geografi bagi Guru MGMP Geografi di Sumatera Barat - Arie Yulfa; Ernawati Ernawati; Dian Adhetya Arif; Bigharta Bekti Susetyo; Bayu Wijayanto; Adek Andreas; Firma Maulidna; M. Mursyid Alfahri (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Relevant media is needed to support the achievement of indicators in the learning process. The purpose of making the Geo-Augmented Reality SOP module is that schools will be skilled in using and utilizing Geo-AR media in geography learning. This Geo-AR media really helps students and teachers to understand teaching material better and it is hoped that making modules in the use of Geo-AR can make it easier for Geo-AR media users. So, it is necessary to develop Standard Operating Procedures (SOP) based on 4D development that support learning. The aspect of internalizing understanding of material and values ​​will increase as the Geo-AR media used can be felt and used by students in 4 Dimensional form. Devotion in the form of developing SOP Geo-AR is used to make it easier to prepare learning designs that can provide an overview of field conditions in real time. Making this media-based learning module is urgently needed to achieve indicators of achievement in the geography learning process that has been designed. The results of this development are module products, training and socialization to community service partner schools.